A Preliminary Bibliography of Polish Publications Concerning the Dead Sea Scrolls (from 1947 to the Spring of 2022) - Klukowski, Michał (The Biblical Annals, 2023)
This publication presents a preliminary bibliography of material on the Dead Sea Scrolls for the years 1947–2022 (spring), which includes only Polish authors’ works which were published. The bibliography has been divided into four parts. The first part gives a list of recent Polish bibliographies, the second one contains monographs and collective works, the third one comprises book chapters and articles appearing in collective works, and the fourth part – papers published in periodicals. The entire work is preceded by a list of abbreviations.